Vitamin D Deficiency as a Predictor of a High Prevalence of Coronary Artery Disease in Pancreas Transplant Candidates With Type 1 Diabetes - Buksińska-Lisik, Małgorzata; Kwasiborski, Przemysław J.; Ryczek, Robert; Lisik, Wojciech; Mamcarz, Artur (Frontiers in Endocrinology, 2021)
Introduction Pancreas transplantation is a high-risk procedure in terms of cardiovascular complications. Therefore, identification of all cardiovascular risk factors is crucial to prevent cardiovascular complications after pancreas transplantation. Vitamin D deficiency (VDD) appears to be a potential risk factor for coronary artery disease. Objective To determine the prevalence of VDD in pancreas transplant candidates, and further to examine the relationship between vitamin D and the prevalence of coronary artery disease and lipid profile parameters. Materials and Methods This is a prospective cross-sectional study. We enrolled consecutive patients with type 1 diabetes eligible for simultaneous pancreas-kidney transplantation or pancreas transplant alone. The laboratory tests included HbA1c, lipid profile, creatinine, and total 25-hydroxyvitamin D (25(OH)D). The diagnosis of coronary artery disease was based on coronary angiography. Results The study population included 48 patients. VDD was revealed in 48% of patients and coronary artery disease in 35% of patients. The mean concentration of vitamin D in the entire cohort was 21.3 ± 9.48 ng/ml. The median value of 25(OH)D in patients with coronary artery disease was significantly lower than in patients without coronary artery disease (18.5 (11.6–21.5) vs. 24.8 (18.4–31.8) ng/ml, p = 0.018). There was a significant relationship between VDD and coronary artery disease (OR = 4.36; 95% confidence interval (CI): 1.22–15.64, p = 0.034). A patient’s odds of having coronary artery disease while having a sufficient level of vitamin D was 4.36 times lower than if the patient had VDD. There was a significant relationship between VDD and hypertension (OR = 5.91; 95% CI: 1.12–31.20, p = 0.039) and hemodialysis (OR = 4.25; 95% CI: 1.25–14.5, p = 0.023). There was no significant correlation between 25(OH)D and lipid profile. Conclusions VDD is highly prevalent in pancreas transplant candidates with type 1 diabetes. There is a significant relationship between VDD and increased prevalence of coronary disease. The lack of any significant association between serum vitamin D and lipid profile suggests that the relationship between vitamin D and coronary artery disease results from other causes.